Az akadémiai közgazdasági gondolkodás formálódása a politika "bordásfalán": Időutazás az ötvenes és a hosszantartó hatvanas évekbe; The formation of the academic economics in the fifties and sixties - Csató Katalin (Hungarian Academy of Sciences, Institute of Economics, 2019)
– My intention was to add my own research to the history of the field of economic research at the Institute of Economics of the Hungarian Academy of Sciences in the period of '50s and '60s. However, the collected material gradually revealed several aspects of István Friss' efforts to try completely controlling the empirical research programme of socialist economic management at the institute founded and headed by him from 1954 to 1974. He was one of the former rákosist and kádárist party leaders and held significant positions in academic life on committees, on controlling economic institutions and publications. He was deeply committed to the politics of Communist Party, particularly to its dogmatic wing, but as an economic-policy maker he understood quite well and accepted that the economic mechanism should be changed towards a market system. He accepted the idea of a "regulated market economy" and the "scientific planning" of the macro-economy. Some researchers indicated at a relatively early stage in the second half of the 1950s, that the over-centralisation of the economic administration was responsible for most of the malfunctioning of the Hungarian economy. Few of the researchers seemed to reject the socialist economic system as a whole. It can also be attributed to Friss that these harsher critical voices of empirical research in the mid-fifties gradually shifted to the idea of transforming the economic mechanism. The "frames" of the reform narrowed or expanded as the power relationships changed in Moscow. Nevertheless, when Friss had to choose between his political loyalty and his professionalism, and that occurred many times during his life, his political loyalty got priority.
Keywords: B24; B25; 330; the history of the Hungarian academic economics; the Institute of Economics of the Hungarian Academy of Sciences; empirical research program in the 1950s and 1960s; reform of economic mechanism; István Friss